Inter-methodological quantification of the target change for performance test outcomes relevant to elite female soccer players - Datson, N.; Lolli, L.; Drust, B.; Atkinson, G.; Weston, M.; Gregson, W. (Science and Medicine in Football, 2022)
Introduction: Valid and informed interpretations of changes in physical performance test data are important within athletic development programmes. At present, there is a lack of consensus regarding a suitable method for deeming whether a change in physical performance is practically relevant or not.